Systems Genetics of Optic Nerve Axon Necrosis During Glaucoma - Stiemke, Andrew B.; Sah, Eric; Simpson, Raven N.; Lu, Lu; Williams, Robert W.; Jablonski, Monica M. (Frontiers in Genetics, 2020)
In this study we identify genomic regions that modulate the number of necrotic axons in optic nerves of a family of mice, some of which have severe glaucoma, and define a set of high priority positional candidate genes that modulate retinal ganglion cell (RGC) axonal degeneration. A large cohort of the BXD family were aged to greater than 13 months-of-age. Optic nerves from 75 strains and the DBA/2J (D2) parent were harvested, sectioned, and stained with p-phenylenediamine. Numbers of necrotic axons per optic nerve cross-section were counted from 1–10 replicates per genotype. Strain means and standard errors were uploaded into GeneNetwork 2 for mapping and systems genetics analyses (Trait 18614). The number of necrotic axons per nerve ranged from only a few hundred to more than 4000. Using conventional interval mapping as well as linear mixed model mapping, we identified a single locus on chromosome 12 between 104 and 116 Mb with a likelihood ratio statistic (LRS) of 19.1 (p genome-wide 0.1). Axon necrosis is not linked to locations of major known glaucoma genes in this family, including Gpnmb, Tyrp1, Cdh11, Pou6f2, and Cacna2d1. This indicates that although these genes contribute to pigmentary dispersion or elevated IOP, none directly modulates axon necrosis. Of 337 positional candidates, nine genes—serine proteinase inhibitor, clade A, member 3G (Serping3g); CDC42 binding protein kinase beta (Cdc42bpb); eukaryotic translation initiation factor 5 (Eif5); BCL2-associated athanogene 5 (Bag5); apoptogenic 1, mitochondrial (Apopt1); kinesin light chain 1 (Klc1); X-ray repair cross complementing 3 (Xrcc3); protein phosphatase 1, regulatory subunit 13B (Ppp1r13b); and transmembrane protein 179 (Tmem179)—passed stringent criteria and are high priority candidates. Several candidates are linked to mitochondria and/or axons, strengthening their plausible role as modulators of ON necrosis. Additional studies are required to validate and/or eliminate plausible candidates. Surprisingly, IOP and ON necrosis are inversely correlated across the BXD family in mice >13 months-of-age and these two traits share few genes among their top ocular and retinal correlates. These data suggest that the two traits are independently modulated or that a more complex and multifaceted approach is required to reveal their association.